Maintenance of Bodily Expressions Modulates Functional Connectivity Between Prefrontal Cortex and Extrastriate Body Area During Working Memory Processing - Jie Ren; Mingming Zhang; Shuaicheng Liu; Weiqi He; Wenbo Luo (Brain Sciences)
Background/Objectives: As a form of visual input, bodily expressions can be maintained and manipulated in visual working memory (VWM) over a short period of time. While the prefrontal cortex (PFC) plays an indispensable role in top-down control, it remains largely unclear whether this region also modulates the VWM storage of bodily expressions during a delay period. Therefore, the two primary goals of this study were to examine whether the emotional bodies would elicit heightened brain activity among areas such as the PFC and extrastriate body area (EBA) and whether the emotional effects subsequently modulate the functional connectivity patterns for active maintenance during delay periods. Methods: During functional magnetic resonance imaging (fMRI) scanning, participants performed a delayed-response task in which they were instructed to view and maintain a body stimulus in working memory before emotion categorization (happiness, anger, and neutral). If processing happy and angry bodies consume increased cognitive demands, stronger PFC activation and its functional connectivity with perceptual areas would be observed. Results: Results based on univariate and multivariate analyses conducted on the data collected during stimulus presentation revealed an enhanced processing of the left PFC and left EBA. Importantly, subsequent functional connectivity analyses performed on delayed-period data using a psychophysiological interaction model indicated that functional connectivity between the PFC and EBA increases for happy and angry bodies compared to neutral bodies. Conclusions: The emotion-modulated coupling between the PFC and EBA during maintenance deepens our understanding of the functional organization underlying the VWM processing of bodily information.